Neurogenic orthostatic hypotension: chasing "the fall". Issue 987 (29th January 2008) - Gupta, D; Nair, M D
Abstract : Orthostatic hypotension (OH) is a frequently encountered problem affecting nearly 30% of the population aged more than 60 years. It can result from neurological and non-neurological derangements which compromise the perfusion of the brain in an erect posture. Neurogenic OH is a manifestation of autonomic failure. It is an important cause of recurrent falls in the elderly, syncopal events and also has been shown to be associated with increased long term mortality from vascular and non-vascular causes. This review will discuss the pathophysiology, aetiology, clinical features and management of neurogenic OH and its differentiation from OH caused by non-neurological causes at each step. A clinician should primarily look for any reversible causes in a patient with neurogenic OH and should not forget that treatment is aimed at restoring the functioning capability of the patient rather than normotension. Co-existent supine hypertension in some patients should be taken into account while treating them.